CA125 Level Association With Chemotherapy Toxicity and Functional Status in Older Women With Ovarian Cancer - Won, Elizabeth; Hurria, Arti; Feng, Tao; Mohile, Supriya; Owusu, Cynthia; Klepin, Heidi D.; Gross, Cary P.; Lichtman, Stuart M.; Gajra, Ajeet; Tew, William P. (International journal of gynecological cancer, 2013)
ObjectiveOlder women with ovarian cancer have increased cancer-related mortality and chemotherapy toxicity. CA125 is a sensitive biomarker for tumor burden. The study evaluates the association between CA125, geriatric assessment (GA), and treatment toxicity.MethodsThis is a secondary subset analysis of patients 65 years or older with ovarian cancer accrued to a multicenter prospective study that developed a predictive toxicity score for older adults with cancer. Clinical and geriatric covariates included sociodemographics, GA (comorbidity, social support, functional, nutritional, psychological, cognitive status), treatment, and laboratory studies. Using bivariate analyses, we determined the association of abnormal CA125 (≥35 U/mL) with baseline GA, grades 3 to 5 toxicity (Common Terminology Criteria for Adverse Events version 3), dose adjustments, and hospitalization. Logistic regression analysis was used to check for potential confounder for association between CA125 and chemotherapy toxicity.ResultsFifty-one (10%) of 500 patients accrued to the primary study had a diagnosis of ovarian (92%), peritoneal (4%), or fallopian tube (4%) cancer. Median age was 72 years (range, 65–86 years). Forty-six patients (90%) had stage III-IV disease. Twenty-three patients (45%) received first-line chemotherapy, and 34 (67%) received platinum-doublet therapy. Thirty-six (71%) had an abnormal CA125. Grades 3 to 5 toxicity occurred in 19 patients (37%). Abnormal CA125 was associated with assistance with instrumental activities of daily living (P < 0.05), lower performance status (P = 0.05), grades 3 to 5 toxicity (P = 0.03), nonheme toxicity (P = 0.04), and dose reductions (P = 0.01). No association between CA125 level and total toxicity score was observed.ConclusionsAmong older women with ovarian cancer, abnormal CA125 was associated with poor pretreatment functional status and an increased probability of chemotherapy toxicity and dose reduction.